ANALISIS NILAI SEWA RUKO STIE CENDEKIA KARYA UTAMA SEMARANG (STUDI KASUS DI KECAMATAN CANDISARI KOTA SEMARANG) (STIE Cendekia Karya Utama, 2022)
The purpose of this study was to determine the rental value of the shop houses of the Cendekia Karya Utama Semarang School of Economics, which are located on Jalan Tegalsari Raya No. 102, Candi Subdistrict, Candisari District, Semarang City. This study uses a market approach. The type of data used is qualitative secondary data. The comparative data used is a similar shophouse which has the same characteristics as the shop for the Cendekia Karya Utama College of Economics. The results showed that the market value for renting a shop shop at the Cendekia Karya Utama Semarang School of Economics using a market approach was Rp. 139,438,889 (spelled out: one hundred thirty-nine million four hundred thirty-eight thousand eight hundred and eighty-nine rupiah) with a rounding result of Rp. 139,450,000 (spelled out: one hundred and thirty-nine million four hundred and fifty thousand rupiah) for one year. Basically, a rental value is guided by the principles related to the market. So, the basis for determining the rental value of the shop houses from the College of Economics Cendekia Karya Utama Semarang is the existence of factors that influence in determining and determining the rental value of the object of assessment. Factors that influence the rental price of property which then results in the market value of land and the market value of the building for the object of research. Factors that affect this value are: land area, building area, title (ownership certificate), location, road width in front of the object, parking area, building age.